2020
DOI: 10.13106/jafeb.2020.vol7.no10.443
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of E-Training, E-Leadership, and Work Life Balance on Employee Performance during COVID-19

Abstract: This study aims to add insight into the effectiveness of e-training, e-leadership, work-life balance, and work motivation on millennial generation employees' performance in today's work life amid the outbreak of the COVID-19 pandemic that requires to work more online. Unlike previous generations, millennials are technology-literate, intent on succeeding quickly, give up easily, and seek instantaneous gratification. The population in this study are millennial generation employees at one of Honda motorcycle deal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 22 publications
5
68
0
12
Order By: Relevance
“…Several studies conducted in Indonesia also show that training has a positive correlation with performance (Constantine et al, 2009;Tanang & Abu, 2014). This is in line with the research findings of Wolor et al (2020) that show that e-training has a positive effect on employee's performance.…”
supporting
confidence: 74%
“…Several studies conducted in Indonesia also show that training has a positive correlation with performance (Constantine et al, 2009;Tanang & Abu, 2014). This is in line with the research findings of Wolor et al (2020) that show that e-training has a positive effect on employee's performance.…”
supporting
confidence: 74%
“…Long before the pandemic, the current research found that work-life balance has a positive influence on the level of job satisfaction of employees (Putra et al, 2020). Worklife balance has a positive role in supporting the improvement of job satisfaction (Wolor et al, 2020;Gigauri, 2020) and work motivation which also plays a role in achieving job satisfaction. A positive attitude can make motivation levels higher and trigger job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Kedua, etraining, kepemimpinan transaksional, work-life balance, dan motivasi kerja berpengaruh positif terhadap kinerja karyawan. Temuannya menunjukkan bahwa perusahaan harus memperhatikan faktor e-training, kepemimpinan transaksional, dan work-life balance agar karyawan tetap termotivasi dan menjaga kinerja karyawan yang optimal, terutama pada saat terjadi pandemi COVID-19 melalui kerja online (Wolor, Solikhah, Fidhyallah, & Lestari, 2020).…”
Section: Pembahasan Penelitianunclassified